Term structure and the sluggishness of retail bank interest rates in euro area countries - Gabe de Bondt; Benoît Mojon; Natacha Valla (European Central Bank (ECB), 2005)
This paper analyses the pricing of bank loans and deposits in euro area countries. We show that retail bank interest rates adjust not only to changes in short term interest rates but also to long-term interest rates. This result, which is arguably intuitive for long-term retail bank rates, is also confirmed for bank interest rates on short-term instruments. The transmission of changes in short-term market interest rates along the yield curve is found to be a key factor explaining the sluggishness of retail bank interest rates. We also show that in the cases where we cannot reject that the adjustment of retail rates has changed since the introduction of the euro, this adjustment has become faster.
Keywords: E43; G21; 330; Euro area countries; market interest rates; retail bank interest rates; Zinsstruktur; Eurozone; Schätzung; EU-Staaten